Comparison of component and quality changes between soft rice and common rice during aging - Wang, Yihang; Wu, Chunsen; Liu, Guodong; Guo, Lunan (Frontiers in Nutrition, 2025)
BackgroundCompared to common rice, soft rice is characterized by low amylose content, soft and elastic texture, and low retrogradation of cold rice. However, the differences of quality deteriorate during aging between soft rice and common rice are still unclear.MethodsIn this study, representative soft rice varieties (NJ9108 and NJ46) were chosen as research subjects, and YJ7081 and HD5 were chosen as control. The changes of their components and quality during aging were comprehensively investigated.ResultsDuring aging, the total starch, fat, and protein content of soft rice decrease, while the amylose content increases. The short-range ordered structure of soft rice starch and the secondary structure of proteins gradually degrade with the extension of aging time. In addition, the relative crystallinity of soft rice starch gradually decreases during the aging process. After aging for 24 M, the average taste value of soft rice decreased by 14.86, and the average 2-AP content decreased by 167.82 ng/g. The average taste value of common rice decreased by 12.52, and the average 2-AP content decreased by 140.42 ng/g.ConclusionCompared to common rice, the component contents and the starch short-range ordered structure characteristics of soft rice exhibited more pronounced changes, leading to increased deterioration of cooking, eating, and aroma qualities during aging.